Educazione e profezia: il rimbalzo della Pedagogia degli Oppressi dentro i canali del dissenso cattolico nell’Italia degli anni Settanta - Todaro, Letterio (Studi sulla Formazione/Open Journal of Education, 2024)
The essay highlights the relevance of the cultural movements gathered around the so-called area of the Catholic Dissent in relation to the first reception of Freire’s pedagogy in Italy, starting from the early Seventies. Actually, the cultural space representing the Catholic Dissent represented a privileged area in the endorsement of Freire’s Pedagogy of the Oppressed in the Italian context. In so far, the reception of Freire’s perspectives on education contributed to strengthen the reasons for the rejection of an oppressive system of education dependent on the exertion of the Power. Along this lines, Freire’s discourse was engaged in participating with a larger struggle for redefining the positions of the Christian conscience in modern times.